Pengembangan Perangkat Pembelajaran pada Materi Interaksi Makhluk Hidup dengan Lingkungan Ditinjau dari Kemampuan Pemecahan Masalah dan Berfikir Kritis Siswa SMP Negeri 2 Moga - Adi Winarso; Joko Siswanto; Fenny Roshayanti (Jurnal Kualita Pendidikan, 2023)
One effort to improve the quality of science learning is how to teach students about critical thinking and problem solving. Critical thinking and problem solving are trained in this study include the ability to formulate problems, provide arguments, do deduction, do induction, and conduct evaluations in learning process. The purpose of this study is to determine student mastery learning, ability to solve the problem, and responses to the implementation of learning tools in material of Living Things and Environment sub-section of Pollution and Environmental Preservation. The design this research is pretest-posttest one group pre experiment using N-gain index. The subjek of this study is 32 students of Grade VII SMP Negeri 2 Moga. The results of this study indicate that the application of learning tools can train students' critical thinking skills and problem solving abilities. This is shown from the completeness of student learning by 83.3%. Most students give positive responses and assume the larning tools are used.